Studi Mengenai Kepuasan Pernikahan pada Pasangan Suami Istri yang Menikah Melalui Ta'aruf di Bandung - Ihsana Sabriani Borualogo; Rahmatinna Rahmatinna (Universitas Islam Bandung, 2011)
There is a way to get to know the opposite sex without courtship called Ta’aruf. Not many people who choose this way of acquaintance. But there are peculiarities in this Ta’aruf process until marriage which interesting to explore descriptively. In the process Ta’aruf, both side are not be able to see each other unless there is a third party as a mediator, someone who trusted by both sides. Every married couple wants to feel the happiness of marriage. Ta’aruf married couples hope to get happiness not only in the world but in the hereafter as well. Marital happpiness associated with the presence of marital satisfaction. According to Douglas K. Snyder (SOURCE) marital satisfaction can be seen through the 12 aspects. The aim of this study is to describe the marital satisfaction in couples who get married through Ta’aruf. The number of subjects is 9 pairs (18 people) and live in Bandung. The data was collected using a marital satisfaction measure was adapted from standard gauge Douglas K. Snyder. The results of validity and reliability of measuring devices such adaptions are as follows: there are 81 valid items with relliability based on Cronbach norm 0.963. Data processing results show 77.7% of married couples through Ta’aruf having marital satisfaction. This is supported by data Conventionalization 66.65%, 83.33% of Global Stress, 77.77% Affective Commuication, Problem Solving 77.77%, Aggresion 55.55%, 66.65% Time Together, Disagreement About Finances 77.77%, Sexual dissatisfaction 66.65%, 77.77% Role Orientation, Family History of Distress 66.65%, 88.88% dissatisfaction with Children, Conflict over Child Rearing 72.21%. The data suggest that the experience of past and present contribute in improving marital satisfaction in couples who married through Ta’aruf.